2020
DOI: 10.3126/janr.v3i1.27170
|View full text |Cite
|
Sign up to set email alerts
|

Seed-borne infestation and management of Alternaria Species in mustard seed at Chitwan district, Nepal

Abstract: Alternaria blight in mustard cause heavy damage to the foliar parts resulting into poor growth and development of plants and thereby reduces seed yield.  Inorder to manage Alternaria infestation in mustard seed for yield maximization, an experiment was conducted in the plant protection laboratory in Nepal Polytechnic Institute, Bharatpur, Chitwan in 2018, using Completely Randomized Design (CRD) with four replicates. Five treatments i.e.Uthane M-45 (2g/kg), Neem powder (3 g/kg), Bojho powder (4g/kg), Trichoder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…A study in Nepal also documented a pathogen incidence of 42.5% Alternaria spp. on mustard seeds after seven days' incubation (Rijal et al, 2020). The present study showed an increased Alternaria occurrence of 58.2% on average in mustard seeds.…”
Section: 13supporting
confidence: 66%
“…A study in Nepal also documented a pathogen incidence of 42.5% Alternaria spp. on mustard seeds after seven days' incubation (Rijal et al, 2020). The present study showed an increased Alternaria occurrence of 58.2% on average in mustard seeds.…”
Section: 13supporting
confidence: 66%